Españoles fuera de España. Historia y memoria de la última ola migratoria española (1945-1980) - María José Fernández Vicente (Amnis)
The’80s have seen Spain transformed from an “Emigration country” to an “Immigration land”. Often submerged by this new situation and its conflictive dimension, Spanish society seems to have forgotten that Spain has been a “land of emigrants”. This work wants to contribute to recover a part of the history-memory of the last Spanish migratory wave. Taking the richness and the complexity of oral sources as a starting point, I try to reconstitute the reasons for Spanish emigration. However, considering the impossibility to embrace the whole migratory flow, I will compare the most important destinations: Argentina, for “the ultramarine” wave (1945-1955) and France for the “continental” one (1956-1980).